Acute fetal asphyxia after gastric rupture in a pregnant patient with a gastric band. (7th October 2013) - Policiano, Catarina; Rocha, Pedro; Catanho, Maria C.; Pinto, Luísa; Valentim‐Lourenço, Alexandre; Graça, Luís M.
Abstract We report a 37‐year‐old primigravida with a gastric band who developed the clinical picture of abdominal pain, vomiting and regurgitation coexistent with a cardiotocogram with severe variable decelerations with absent variability at 33 weeks' gestation. After partial improvement with gastric band enlargement, new aggravation of symptoms and recurrence of a pathological cardiotocogram led to an emergency cesarean section. Intraoperatively, hemoperitoneum from gastric rupture was verified and partial gastrectomy was performed. After bariatric surgery, pregnant women are at increased risk of gastrointestinal complications, which may need prompt and multidisciplinary diagnosis and management in order to avoid maternal–fetal morbidity and mortality.